Poverty, growth and redistribution: A case study of Iran - Ahmad Assadzadeh; Satya Paul (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2001)
This study examines the changes in the extent of poverty in Iran during the post-Islamic period. More specifically, it investigates the contributions of growth and redistribution factors to changes in poverty over a period of ten years (1983 to 1993). The analysis is based on household level data relating to three consecutive household income and expenditures surveys of 1983, 1988 and 1993. The study reveals that over a period of ten years, the extent of poverty in the rural area has declined slightly, whereas in the urban sector it has increased by more than 40 percent. The alarming rate of increase in urban poverty necessitates calls for a greater attention from the government to initiate effective poverty alleviation programs. The decomposition of over-time changes in poverty into growth and redistribution components indicates that in each sector the redistribution component was positive during 1983-93, implying that the deterioration of the income inequality contributed to the worsening of poverty. Growth component, however, affected the two sectors differently. Between 1983 and 1993, the growth component for the rural sector was negative, contributing to the decline in poverty. For the urban sector, it was positive, assisting to raise the level of poverty. In addition, there are large variations in the levels of poverty across regions and occupations in Iran. – poverty ; growth ; redistribution ; Iran
Keywords: I31; I32; 330; Armut; Einkommensverteilung; Wirtschaftswachstum; Iran